Bone induction at physiological doses of BMP through localization by clay nanoparticle gels. (August 2016) - Gibbs, D.M.R.; Black, C.R.M.; Hulsart-Billstrom, G.; Shi, P.; Scarpa, E.; Oreffo, R.O.C.; Dawson, J.I.
Abstract: Bone Morphogenic Protein 2 (BMP2) can induce ectopic bone. This ability, which first motivated the widespread application of BMP2 in fracture healing and spinal arthrodesis has, more recently, been indicated as one of several serious adverse effects associated with the supra-physiological doses of BMP2 relied upon for clinical efficacy. Key to harnessing BMPs and other agents safely and effectively will be the ability to localize activity at a target site at substantially reduced doses. Clay (Laponite) nanoparticles can self assemble into gels under physiological conditions and bind growth factors for enhanced and localized efficacy. Here we show the ability to localize and enhance the activity of BMP2 to achieve ectopic bone formation at doses within the sub-microgram per ml range of concentrations sufficient to induce differentiation of responsive cell populations in vitro and at approximately 3000 fold lower than those employed in clinical practice.